Home inventory administration manual - Cadwell, Bettye; Bradley, Robert (Arkansas: Minuteman Press, 2003)
Contents:The HOMEs: Learning to use the Home. Administering the infant / todder HOME (IT-HOME). Administering the early childhhod Home (EC-HOME). Administering the middle childhood Home (MC-HOME). Administering the early adolescent Home (EA-HOME). Administering the child care infant / Toddler HOME (CC-IT-HOME). Administering thw child care early childhood HOME (CC-EC-HOME). Introduction to the disability adaptations of the HOME. Administering the disability-adapted infant / toddler HOMEs (DA-IT-HOMEs). Administering the disability-adapted early childhood HOMEs (DA-EC HOMEs). Administering the disability-adapted middle childhood HOMEs (DA-MC HOMEs). Epilogue. Statictics